2022
DOI: 10.2174/1874467215666220127115602
|View full text |Cite
|
Sign up to set email alerts
|

Humanin Ameliorates Late-onset Hypogonadism in Aged Male Rats

Abstract: Background: The reproductive potential declines with age. Late-onset hypogonadism is characterized by reduced serum testosterone. Humanin is a mitochondrial-derived signaling peptide encoded by short open reading frames within the mitochondrial genome. It may protect against some age-related diseases such as atherosclerosis by its cytoprotective effects. Objective: it aimed to investigate the potential anti-aging effects of humanin on the testicular architecture, oxidative stress, some apoptotic and inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Moreover, Gottardo et al [ 29 ] demonstrated that HN inhibited apoptosis induced by TNF- α in anterior pituitary cells of male and female rats that had undergone gonadectomies. A further support to our data, El Kattawy et al [ 24 ] proved that HN has anti-aging properties and anti-apoptotic as HN elevated PCNA and BCL2 activity and reduced testicular caspase-3 activity and suppressed pro-apoptotic BAX protein expressions in the aged rats.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Gottardo et al [ 29 ] demonstrated that HN inhibited apoptosis induced by TNF- α in anterior pituitary cells of male and female rats that had undergone gonadectomies. A further support to our data, El Kattawy et al [ 24 ] proved that HN has anti-aging properties and anti-apoptotic as HN elevated PCNA and BCL2 activity and reduced testicular caspase-3 activity and suppressed pro-apoptotic BAX protein expressions in the aged rats.…”
Section: Discussionsupporting
confidence: 91%
“…The obtained data were represented as mean ± standard error (SE) using statistical package for social science software (SPSS, Chicago, IL, version 20). The mean difference significance between the studied groups was obtained using one-way analysis of variance (ANOVA test) followed by post hoc test LSD test for pairwise comparison of the means of the different studied groups [60], with significance level set at p˂0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Other putative antioxidants such as Korean red ginseng ( Kopalli et al , 2017 ), Cordycepin ( Kopalli et al , 2019 ), Gigantol ( Basque et al , 2021 ), and vitamin C ( Heidari et al , 2023 ) have similar effects. The source of oxidative stress in ageing Leydig cells is thought to be mitochondrial ( Chen et al , 2001 ; Miquel, 2002 ; El Kattawy et al , 2022 ), while the target is thought to be the hormone-sensitive mitochondrial cholesterol transfer step of steroidogenesis ( Diemer et al , 2003 ).…”
Section: Paternal Ageing Testosterone and Oxidative Stressmentioning
confidence: 99%